2021
DOI: 10.1101/2021.07.18.452836
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

EEG biomarkers of reduced inhibition in human cortical microcircuits in depression

Abstract: Major depressive disorder (depression) is a complex condition that involves multiple physiological mechanisms, spanning a range of spatial scales. Altered cortical inhibition is associated with treatment-resistant depression, and reduced dendritic inhibition by somatostatin-expressing (SST) interneurons has been strongly implicated in this aspect of the pathology. However, whether the effects of reduced SST inhibition on microcircuit activity have signatures detectible in electroencephalography (EEG) signals r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 123 publications
(287 reference statements)
1
28
0
Order By: Relevance
“…Our results demonstrated that α5-PAM could directly recover function and resting state EEG features associated with a loss of SST-mediated inhibition in depression (Mazza et al 2022;Yao et al 2022), despite only boosting SST→Pyr synapses and not SST→PV and SST→VIP synapses, which were also reduced in our depression models. This is likely because the loss of SST interneuron inhibition in depression has a direct and thus much larger impact on Pyr neurons than the indirect disinhibitory effect of reduced SST interneuron inhibition onto interneurons.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Our results demonstrated that α5-PAM could directly recover function and resting state EEG features associated with a loss of SST-mediated inhibition in depression (Mazza et al 2022;Yao et al 2022), despite only boosting SST→Pyr synapses and not SST→PV and SST→VIP synapses, which were also reduced in our depression models. This is likely because the loss of SST interneuron inhibition in depression has a direct and thus much larger impact on Pyr neurons than the indirect disinhibitory effect of reduced SST interneuron inhibition onto interneurons.…”
Section: Discussionmentioning
confidence: 57%
“…As in previous studies, we used models of human cortical L2/3 microcircuits to study effects on cortical microcircuit function (Yao et al 2022) and EEG signal (Mazza et al 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it has been suggested that GABAergic deficit may play a central role in the etiology of MDD, especially in melancholic (17) and treatment-resistant types of depression (18).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, however, it has been shown that the slope of the aperiodic component reflects the ratio between excitatory and inhibitory currents in the brain (12). Given the crucial role of the proper balance between neural excitation and inhibition (E/I) for healthy cognition, behavior (13) and sleep, aperiodic activity seems to be a promising tool for investigating MDD with its cholinergic, monoaminergic (14,15), glutamatergic (16) and GABAergic imbalance (17,18). In MDD, the E/I ratio could be further affected by prescribed antidepressants.…”
Section: Introductionmentioning
confidence: 99%